Career Progression of Women: Does Work Life Balance Matter? - Emmanuel Essandoh; Isaac Tetteh Kwao; Barbara Arthur; Doris Akalachiba Asandem; Emmanuel Agyenim Boateng (European Scientific Journal, ESJ, 2023)
Purpose-The study empirically examined the influence of work-life balance practices on Career Progression of Women at Ministry of Gender, Children and Social Protection (MoGCSP). Design, methodology/approach-Given the reliance on explanatory research design, the study utilized structured questionnaire for gathering the primary data quantitatively from 209 randomly selected participants. A second-order model was configured in SMART PLS for testing of the directional hypotheses formulated. Findings- Work-life balance practices have a moderate significant positive predictor on both career goal progress and promotion speed. However, it significantly predicts a weak positive variance in professional development ability of career progression. Research limitations- The study was limited to only female MoGCSP employees, and this may restrict the degree of generalizability to other ministries of the government of Ghana. Practical implication- The Ministry of Gender, Children and Social Protection through its agency, must continually provide a favourable work life balance practices for its female staff as this would in order to make female workers happy, satisfied and progressed in the various careers. Originality/value- Empirically, the study enriches the theoretical understanding of how work-life balance if properly managed would affect female workers in progression in their career even in a masculine context as established by the role theory in Sub-Saharan country-context.